Touch and go a memoir - Terkel, Studs 1912-2008 (New Press, 2007)
At nearly 95, Studs Terkel has written about everyone's life, it seems, but his own. Here he offers a memoir which--embodying the spirit of the man himself--is youthful and vivacious. Terkel begins by taking us back to his childhood, describing the hectic life of a family trying to earn a living in Chicago. He then goes on to his experiences--as a poll watcher charged with stealing votes for the Democratic machine, as a young theatergoer, and eventually as an actor himself in both radio and on the stage--giving us a portrait of the Chicago of the 1920s and 1930s. He tells of his beginnings as a disc jockey after World War II and as an interviewer and oral historian--a craft he would come to perfect. Finally, he discusses his involvement with progressive politics, leading to his travails during the McCarthy period when he was blacklisted.--From publisher description